The Role of Routine Clinical Pretreatment 18F-FDG PET/CT in Predicting Outcome of Colorectal Liver Metastasis. (May 2015) - Tam, Henry H.; Cook, Gary J.; Chau, Ian; Drake, Brent; Zerizer, Imene; Du, Yong; Cunningham, David; Koh, Dow-Mu; Chua, Sue S.C.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to determine the value of SUV-based metabolic parameters derived from pretreatment 18F-FDG PET/CT of colorectal liver metastases in predicting disease response, progression-free survival (PFS), and overall survival (OS). Patients and Methods We retrospectively reviewed 70 colorectal patients with liver metastases who underwent pretreatment 18F-FDG PET/CT. SUVmean, SUVmax, TLG (total lesion glycolysis), metabolic tumor volume, and metabolic tumor diameter were the metabolic parameters derived from volume of interest analysis of the most FDG-avid liver lesion in each subject. Clinical and laboratory parameters were recorded. Tumor response was assessed by response evaluation criteria in solid tumors 1.1 criteria at 12 weeks after treatment. Associations between tumor response, metabolic parameters, and clinical/laboratory parameters were examined by 1-way analysis of variance. The relationship of the metabolic parameters with PFS and OS was determined by Kaplan-Meier analyses and further confirmed with multivariate Cox regression analyses. Results SUVmean less than 4.48, SUVmax less than 6.59, TLG less than 75.2, metabolic tumor volume less than 4.49 cm3, and hemoglobin level greater than or equal to 11 g/dL were associated with longer PFS (P < 0.05). Prior surgery or radiofrequency ablation to the liver metastases was the only additional factor shown to be associated with longer OS. Conclusions SUV-based metabolic parameters derived from pretreatment 18F-FDG PET/CT can predict PFS in colorectal liver metastases.